الثقافــة السياسيــة في الفكر الاجتماعي المعاصر - حبــاسي, خالــد (University of Eloued جامعة الوادي, 2015)
مصطلح " الثقافة السياسية " مصطلح تفسيري يوضح جانبا من أسباب نشأة أي نظام سياسي وفشله أو نجاحه. يرى الغزالي أن الكثرة الغالبة من العاملين في ميدان الفقه تنأى عن الشأن السياسي، ومنهم من يستنكـر أصلا أن يكون هناك علاقة من أي نوع بين السياسة والدين بشكل عام. كما يرى وجوب السعي في تبصير الأمة بشؤونها العامة، وتعريفها بحقوقها وواجباتها، وتربيتها على الحس السياسي، والمشاركة فيه. لأن غياب هذه التربية قد أفرز ما نلاحظه من معوّقات كبرى تسهم في تشويه الثقافة السياسية للأمة، هذه المعوّقات هي: 1.داء النظرة الجزيئية، وعدم قدرة بعض الناس على ترتيب الأولويات. 2.اتسام جمهرة المتدينين بقصور بالغ في الفكر السياسي. 3 ـ تصدر المتزمتين والمتشددين قافلة الشأن السياسي. ومثلما أن للسلطة أثرها ووظيفتها في تحقيق قيم الإسلام، فللجماهير مثل ذلك. Abstract: The term "political culture" is an expository term which explains reasons for the emergence of any political regime ‚ its failure or success. The eminence Ghazali believes that the overwhelming majority of Fiqh scholars are away from politics, and as a matter of fact ‚some of them deny the relationship between politics and religion. He also seeks to enlighten the nation thought with the public affairs by defining rights and duties, and making its political feeling grow into political participation Because the lack of education is a result for all what we observe such as: serious obstacles which mislead the political culture of the nation, consequently they are: first‚ dividing vistion disease , moreover ‚ some people are not being able to prioritize. Second‚ the majer religious persons are weak in sense of political trend. Third‚ extrimists are the upperhands concerning political affairs. As far As the impact of authority and function of It for achieving the values of Islam, and the audience otherwise.
الغزالي أنموذجا
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الثقافة السياسية - الفكر الاجتماعي